The Effecto of Using Deductive Approach and Inductive Approach in Teaching English to Students on Their Conditional Sentence Mastery (An Experimental Study) - Limris Gorat; V. Luluk Prijambodo (Widya Mandala Surabaya Catholic University, 2013)
This study investigates the effect of using deductive and inductive approach in teaching English to students on their conditional sentence mastery. This study also intends to describe the students’ perception toward deductive or inductive teaching approach. This study was a queasy experimental study which compares the effectiveness of deductive and inductive approach in teaching conditional sentences. The sample of this study is 64 SMK students in the academic years of 2012-2013. The students consist of two classes and each class comprises 32 students. The findings indicate that inductive teaching approach is more effective than deductive approach when used to teach conditional sentences. The result of the questionnaire indicates that students like the inductive approach and they are satisfied taught using inductive approach